Functional duties of the police in the face of family violence - Ramos-Pacheco, Pascual Florencio (2022)
This book is an adaptation of an investigation presented to the César Vallejo University, which aimed to analyze what were the difficulties in the financial inclusion of the Municipal Office for Attention to Persons with Disabilities District of Paramonga (Peru). It was a qualitative approach, the type of research was basic, the research design was a case study. Semi-structured interviews, observation and documentary analysis were used as techniques. In addition, the inductive method was used for the development and analysis of information collected within the study unit. The results allowed us to conclude that there are difficulties regarding the financial inclusion of the Municipal Office for Attention to Persons with Disabilities, due to a lack of articulation between public and private organizations due to the lack of adequate information regarding the benefits of financial inclusion. for this social group. There is an effort to achieve this inclusion, as well as a regulatory framework in this regard; but due to the lack of articulation, the implemented strategies do not benefit the population with disabilities in order to achieve their effective inclusion within society.
Keywords: financial inclusion; access; use; quality; disability